Analysis of Factors Hypertension in Online-Based Transportation Driver in Kediri City - Arif Mustofa; Nurwijayanti Nurwijayanti; Rahmania Ambarika (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
One of the actions that can be taken to prevent hypertension is to develop knowledge about the level of vulnerability on several factors that influence it. It is expected that with enough knowledge to feel the level of vulnerability can increase awareness of hypertension. The purpose of this study was to determine the effect of the level of vulnerability on factors of sleep quality, stress, and eating patterns on hypertension in online-based transportation drivers in Kediri City. The research design used is quantitative research using the